A influência dos valores pessoais e atitudes no desejo de compartilhar o conhecimento: um estudo com professores pesquisadores brasileiros - Menezes, Elisabeth Aparecida Corrêa (2012)
The motivation for this thesis arose from a review of the literature on the subject knowledge. This topic is of interest not only of academic institutions as organizations. It is observed that knowledge has been responsible for the evolution of society. The literature review showed that factors such as knowledge as a source of power and grace influence knowledge sharing. Power and benevolence are considered as values (SCHWARTZ, 1992). Values influence behavior through attitudes (ROKEACH, 1981). Models of behavior were designed to predict human behavior. The Model of Goal-Directed Behavior (MGB) is considered a strong predictor of human behavior because it contains variables such as "desire" (TAYLOR; BAGOZZI; GAITHER, 2005). According to this model, "desire", which means the will to act, directly influences the behavior intention and therefore the behavior (PERUGINI; BAGOZZI, 2001). Thus, this study aimed to identify whether the relationship between values (self-enhancement and self-transcendence), knowledge as a source of power and attitudes better explains the desire to share knowledge than attitudes, values, and values associated with attitudes. Given the importance of knowledge sharing in academia, this thesis is devoted to the study in the academic environment, specifically with faculty researchers. This research is characterized as descriptive with quantitative approach. To achieve the objective of this research, it had been used four scales, three developed by the author: "attitudes towards knowledge sharing", "desire to share knowledge" and "knowledge as a source of power," and the scale of Schwartz (1994) Profile of Personal Values in its reduced version, known as PVQ 21. The questionnaires were made available through a website specializing in research, the access link was forwarded by e-mail, reaching 409 valid questionnaires. The scales were tested using exploratory and confirmatory factor analysis, and analysis of the proposed structural model was performed using structural equation modeling. The results showed that the best model to explain the desire to share knowledge was the relationship between self-transcendence values, knowledge as a source of power and attitudes. The results also showed the existence of differences of perception in terms of functional and demographic variables of respondents.